The Effect of Different Fibers on Granite Residual Soil Reinforced with Alkaline Solution - Bingxiang Yuan; Jianhong Liang; Jingkang Liang; Weijie Chen; Baifa Zhang; Wei Chen; Tianying Chen (Advances in Civil Engineering)
This study explores the reinforcement effect of different fibers in an alkaline solution on the mechanical properties of granite residual soil using the single variable method. The macroscopic mechanical properties of the reinforced samples were studied using the unconfined lateral compressive strength test and the drop-weight load test, while the microscopic properties were characterized using techniques such as SME and XRD. The results indicated that the greatest reinforcing effect was attained when the ratio of SiO2/Na2O in the alkaline solution was 0.5 mol with the compressive strength of 4402.85 kPa. At the time, the reinforcing effect of glass fiber in an alkaline solution on granite residual soil was superior to that of basalt fiber. The inclusion of glass fibers and an alkaline solution of 0.5 mol SiO2/Na2O into the granite residual soil exhibited the best capacity for reinforcing, with the maximum impact load and compression reaching 120 kN and 12.1 mm, respectively. The findings of SME analysis revealed that GRS included a significant amount of kaolinite, which, when decomposed in an alkaline solution, generated a gel substance that bound the fibers and soil together and filled the pores between them, thereby enhancing the sample’s compactness. XRD results demonstrated the formation of gel and a small amount of geopolymer in the soil under the alkaline solution of 0.5 mol SiO2/Na2O, which tighten the binding between soil particles and fibers and increase the overall strength.